Effect of physical diet form on productive performance of grower quail - Kesab, Yaser Ghanim Salih (Journal of Kerbala for Agricultural Sciences, 2018)
The aims of this research to evaluate effect of physical diet form : T1(Mash), T2(Pellet) and T3(Crumble) on nutrition of grower quail and their impact on some productive, carcass, blood serum characteristics and economic efficiency. 216 grower Japanese quail (Coturnix coturnix japonica) desert color unsexed divided into 3 treatments, in each one 6 replication with 12 birds, the research start from 2 weeks old with one stage(grower) to end of 6weeks old. The results showed significant differences (P ≤ 0.05) on final body weight, total weight gain, total feed consumption, total feed conversion ratio(g feed : g weight gain ) (g feed : g carcass ), total water consumption, total water conversion ratio (ml : g weight gain ), preslaughter weight, carcass weight, dressing percentage without edible giblets, breast percentage, gizzard percentage, breast pace tenderness and juiciness, thigh pace juiciness, total protein and albumen on blood serum. No significant effect in all other characteristics in the study. The best net return (Iraqi Dinar / Kg live weight) (Iraqi Dinar / Kg carcass weight) for T3 then T2 and last T1. Keys words: diet form, productive performance, blood, economical, grower quail.